1993
DOI: 10.1111/j.1365-2141.1993.tb03181.x
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of aplastic anaemia after immunosuppressive treatment: a report from the European Bone Marrow Transplantation Group SAA Working Party

Abstract: This study was designed to determine the incidence of relapse and factors predictive for relapse in 719 patients with severe aplastic anaemia (SAA) after immunosuppressive treatment (IS). Patients developing myelodysplasia or acute leukaemia after IS, and patients receiving a transplant, were excluded from this analysis. Response was defined as reaching complete independence from transfusions, relapse was defined as becoming again transfusion dependent. This criteria was validated by similar figures when using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 29 publications
5
64
2
1
Order By: Relevance
“…14 A European group reported that the actuarial risk for relapse after IST was 35% at 10 years, and the relapse occurred at any time from a few months to 10 years after IST without a particular period of higher occurrence. 23 Because the median follow-up period of our study was not so long, the possibility that G-CSF only delays the time of relapse cannot be excluded. To elucidate whether G-CSF actually prevents relapse or only delays the time of relapse, further follow-up is required…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 A European group reported that the actuarial risk for relapse after IST was 35% at 10 years, and the relapse occurred at any time from a few months to 10 years after IST without a particular period of higher occurrence. 23 Because the median follow-up period of our study was not so long, the possibility that G-CSF only delays the time of relapse cannot be excluded. To elucidate whether G-CSF actually prevents relapse or only delays the time of relapse, further follow-up is required…”
Section: Discussionmentioning
confidence: 99%
“…14,15 It has been reported that the overall survival in patients who do not relapse is better than that of patients who relapse. 23 Therefore, better survival in the G-CSFϩ group will be expected because of the low incidence of relapse in the G-CSFϩ group. Further follow-up is necessary to conclude whether a difference in overall survival exists between the G-CSFϩ and the G-CSFϪ group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one might want to take additional endpoints such as eventfree survival, the ability to tolerate treatment, and quality of life during different sequences of relevant health states into account in the decision making process, when different treatment options result in similar long-term survival. In aplastic anemia, quality of life outcomes are affected by treatment toxicity, graft rejection, infections, and graft-versus-host disease (GvHD) after BMT [13][14][15], and by persisting cytopenia due to slow or incomplete responses, relapse of aplastic anemia, or the development of clonal disorders such as myelodysplastic syndrome (MDS) or paroxysmal nocturnal hemoglobinuria (PNH) after immunosuppression [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival at 5 years is estimated at about 80%, but the eventfree survival rate is lower as a result of non response or relapse. Relapse, defined as requirement for platelet or erythrocyte transfusions in patients having been transfusion-independent for at least 3 months, occurs in about 30% of patients [27]. In addition, these patients have an increased risk of developing solid tumors and clonal disorders such as myelodysplastic syndromes (most frequently involving chromosomes 7 or 8), acute myeloid leukaemia and paroxysmal nocturnal hemoglobinuria [28].…”
Section: Discussionmentioning
confidence: 99%